2011
DOI: 10.1007/s00234-011-0849-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery variations at the C1–2 level diagnosed by magnetic resonance angiography

Abstract: We frequently observed VA variations at the C1-2 level and with female predominance. The persistent FIA was most prevalent and sometimes seen bilaterally. Preoperative identification of these variations in VA is necessary to avoid complications during surgery at the craniovertebral junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 11 publications
1
44
0
Order By: Relevance
“…If the FIA persists along with the normal VA, it gives rise to fenestration or it may join the future PICA, making its origin anomalous. 7 Apart from these 3 variations we found a fourth; when the VA loops medially before entering the C-1 transverse foramen or the osseous canal (Fig. 6).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…If the FIA persists along with the normal VA, it gives rise to fenestration or it may join the future PICA, making its origin anomalous. 7 Apart from these 3 variations we found a fourth; when the VA loops medially before entering the C-1 transverse foramen or the osseous canal (Fig. 6).…”
Section: Discussionmentioning
confidence: 79%
“…These variations have been described in 1% of the normal population but are quite often seen in those with congenital CVJ anomalies. 7,9 The VA develops from the plexiform anastomoses between 7 cervical intersegmental arter- Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…The C-1 LMS is a common method for C-1 fixation but it is technically demanding, especially when the lateral mass is obscured by a thick posterior arch, 39 ponticulus posticus, 17 anomalous VA, 17,28,35,37 or a large paravertebral venous plexus. 21 Goel et al reported 2 patients who required an alternative method and only 1-side LMS was completed in 9 cases.…”
Section: Discussionmentioning
confidence: 99%
“…7,21,39 If C1-2 was displaced after injury, the PS may exhibit stronger resistance. It was also shown that the incidence of a VA anomaly between C-1 and C-2 in Asia was more common than in the US, and it directly affected the safety of C-1 LMS placement, 17,28,35,37 so fixation must be planned to minimize the VA injury. The choice was also influenced by our clinical experience.…”
Section: 4mentioning
confidence: 99%
“…Women are more likely to exhibit these anomalies (2). A persistent hypogloassl artery (PHA) is the second most common persistent fetal variant behind a persistent trigeminal artery with a prevalence of 0.02 -0.1% in the general population (3).…”
Section: Koleilat and Hanovermentioning
confidence: 99%